Violence and truth - Vidal, Denis (Delhi, 1997)
This is an important and innovative book because it gives the analysis of violence, past and present, an important place in the sociology of India. It is also a strong, if mostly implicit, critique of Dumont's theory of cast, in which violence has no significant place. Trained as an anthropologist, the author distances himself from the accepted concepts in Indian sociology, and offers a different view of society in India.
Keywords: Rajasthan -History